KAITAN ASPEK STATUS SOSIAL PETANI SAYUR TERHADAP JENIS SUMBER INFORMASI YANG DIMANFAATKAN DI KELURAHAN LINGKAR SELATAN KECAMATAN JAMBI SELATAN KOTA JAMBI - Nida Kemala; Wiwin Alawiyah (Universitas Batangahari Jambi, 2016)
AbstractThis research had been held in Lingkar Selatan Village which focusing to learn the description of social status of farmer, information source that used by them and the relationship between those variables. Social status were indikated in three cases e.g. education, land wide and the respodent role in its siciety. There were 41 samples that selected by simple random sampling method. Description method was used to analyzed those variables and Chi–Square 2x2 was applied to analyzed the relationship between them.The result of this research should be expected to be a foundation in deciding by the authority in selecting a agricultural information transfer system which considered the various information sources. Instead of this consideration the information should be correctly transferred. The result of this research showed that the farmer number that has low education category (63%) was higher than the high one (37%). The low category of land wide was dominant (66%). Only three farmers that had authority role and all of them had showed hight category of information source useness. It showed 59% (24 farmers) have hight category of information source useness while 41% (17 farmers) showed low category of it useness and 16 farmers not used electronic information source yet. The farmer authority showed a significant relationship with information source useness, while education dan land wide had no relationship significantly with it. Keyword : Social Status, Extension, Information source, Farmer